DAMPAK LINGKUNGAN DARI KERJASAMA BELT AND ROAD INITIATIVE (BRI) DI PAKISTAN 2016-2019 - Bob Marta; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This paper will explain the environmental impact of the Belt and Road Initiative (BRI) cooperation in Pakistan 2016-2019. BRI in the China-Pakistan Economic Corridor (CPEC) focuses on investment in energy and infrastructure of transportation. The cooperation began in 2015 with 21 energy sector projects, 24 transportation infrastructure projects, 9 special economic zone (SEZ), 14 Gwadar projects, 27 socio-economic development projects, and 3 public sector development projects. A total of 69% of the 21 energy projects comes from coal energy projects without environmentally friendly. Deforestation has also occurred since 2016, as a result of which there has been increasing in carbon emissions that affect the melting of glaciers in Pakistan. Deforestation also causes to be threatened to the quantity of biodiversity. This study uses a descriptive qualitative method. Data collection techniques with literature studies (document analysis). The theory of this research uses Green Political Theory by Andrew Dobson, which is identical with two approaches, namely the rejection of anthropocentrism and growth restriction on the nature of the environmental crisis. The result of this research are CPEC has responsibilities for the increase in carbon emissions by 369,457.2 MTCO2e- which comes from coal energy. Deforestation of 1,362,500 hectares in Punjab, Khyber-Pakhtunkhwa and southwestern Pakistan and led to a glacier melting rate of 0.66 m/yr. In addition, deforestation has also caused of threatened extinction to 10 species of mammals in Pakistan. Keywords: BRI, CPEC, Pakistan, Enviroment, China, Emision